Gestión administrativa del talento humano del colegio Emigdio Esparza Moreno en el periodo 2022 - Recalde Aguáchela, Katherine Paulina (2023)
The administrative management of human talent at the Emigdio Esparza Moreno School is essential to guarantee an efficient and satisfactory educational environment; the selection and hiring of personnel is a key process. The school strives to recruit highly qualified teachers and support staff committed to the educational mission of the institution. An exhaustive evaluation of the candidates' skills and experience is carried out to ensure the quality of the team. Training and continuous professional development are essential. The school offers training and refresher programs for staff, allowing them to keep up to date with educational trends and improve their pedagogical skills. Performance evaluation is a vital tool. Regular reviews of staff performance are carried out to identify strengths and areas for improvement. This allows you to provide constructive feedback and set individual development goals. Effective internal communication is essential. The school promotes an open and collaborative work environment, encouraging communication between all levels of employees. This contributes to team cohesion and efficient problem solving. Human resource management also includes aspects related to compensation and benefits, ensuring that employees are fairly rewarded for their work